Advances in polymer science = Fortschritte der Hochpolymeren-Forschung. 26 - Cantow, H.-J (Springer-Verlag, 1978)
Molecular mobility and relaxation processes in polymers / W. Holzmüller ; The Iso-free-volume state and glass transitions in amorphous polymers: new development of the theory / Y.S. Lipatov ; Model networks / P. Rempp, J.E. Herz, W. Borchard ; NMR approach to the phase structure of linear polyethylene / R. Kitamaru, F. Horii
Keywords: struktura materiálů; polymery; deformace; polyethylen; polymerní sítě